Logistics Management for Service Quality in a company in the gastronomic sector - BRAVO HUIVIN, ELIZABETH KRISTINA; Lewis Zuñiga, Patricio Federico; Trillo Espinoza, Veronica Margarita; Vargas Espinoza, Luis; UGARTE CONCHA, ANGEL ROLAND; Cárdenas Núñez, Beth Evelyn (LACCEI, 2024)
The research studied the relationship between logistics management and service quality in an SME in the Gastronomic Sector of the city of Trujillo in the year 2023. Specific objectives are established to evaluate different aspects of logistics management and its elevation with service quality. The research is classified as applied and uses a quantitative approach. A non-experimental and correlational transectional design was adopted to examine the interrelationships between variables without influencing their modification. The findings revealed a significant correlation (coefficient of 0.822) between logistics management and service quality, suggesting a direct relationship: improvements in logistics management lead to an improvement in service quality. It was concluded that the level of logistics management and quality of service varies between good and average. Furthermore, moderate to high relationships were identified between logistics management and several aspects of service quality, such as tangibility, reliability, responsiveness, security, and empathy. The costs of implementing improvements in logistics management were estimated to improve the quality of service, as well as the social and environmental impact was evaluated, highlighting both economic and resource savings due to more efficient logistics management.